Innovationen, Imitationen und Differenzgewinne: Die Barone-Kurve im Kontext wirtschaftlicher Entwicklung - Friedrich L. Sell (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2019)
– In this paper, we intend so "re-construct" the famous Barone-curve, which goes back to Enrico Barone's contributions to economics in the 1930s. After discussing the comparative statics and the distribution of profits features of the model, we have explicitly introduced, for the first time, the demand side of the economy into the model. This is important when it comes to assess the relevance of major demand factors' elasticities. Thereafter, we have set up a dynamic version of the Barone curve model. Based on a heterogeneous second order differential equation, the stability and convergence properties of prices are identified under the conditions of an existing Barone curve. Finally, we have analyzed possible empirical investigations on the relevance of the Barone curve and evaluated policy implications.
Keywords: B31; B22; E32; O31; O11; O47; 330; Innovation; imitation; Barone curve; Static and dynamic macro modeling